2020
DOI: 10.18697/ajfand.90.19175
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of different forms of fish in Abakaliki metropolis of Ebonyi State, Nigeria

Abstract: Fish represents an important component of protein intake of many households in Nigeria. The different forms of fish available for consumption in most urban areas of Nigeria are fresh, smoked, dried or frozen fish. Households have different preferences for different forms of fish arising from changes in demand, price and income of the household. This creates the need to study and understand the level of demand for the different forms of fish consumed, the factors that influence fish consumption and how the dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
2
4
0
Order By: Relevance
“…This means that household heads with more income consume fish more than their counterparts with low income. This is consistent with a study by Onyeneke et al (2020) who reported that there is a relationship between income level and fish eating. Household size had a negative coefficient of -0.423 at a 10% level of significance.…”
Section: Determinants Of Fish Consumption By Households In the Study ...supporting
confidence: 93%
See 4 more Smart Citations
“…This means that household heads with more income consume fish more than their counterparts with low income. This is consistent with a study by Onyeneke et al (2020) who reported that there is a relationship between income level and fish eating. Household size had a negative coefficient of -0.423 at a 10% level of significance.…”
Section: Determinants Of Fish Consumption By Households In the Study ...supporting
confidence: 93%
“…Married respondents may have larger household size, and hence have more member of the family who consume the fish they buy. This also is in agreement with the report by Onyeneke et al (2020) who reported amongst other demographic factors that household size has positive and significant relationship with fish consumption.…”
Section: Determinants Of Fish Consumption By Households In the Study ...supporting
confidence: 93%
See 3 more Smart Citations